Factors affecting the performance of hotels in Beijing, China. - Kwik, Angeline Wan Yin. (2008)
We look at how star rating, ownership and chain affiliation affect the performance of hotels in Beiing. In addition, we examine the effects of competition and agglomeration on performance. With respect to agglomeration benefits, we address two questions: who generates the agglomeration benefits and who gains from the agglomeration benefits.